The Effect of Supply Disruption Orientation, Supply Chain Quality Management, and Digital Technologies on Supply Chain Resilience and Its Implications on Firm Performance - Wibowo, Muchamad Bagus Satrio; Setiawan, Agung; Santosa, Wahyuningsih; Dewayana, Triwulandari Satitidjati (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This study evaluates the fit of the tested model with the existing data through goodness of fit analysis. Although the p-value is very small and fit indicators such as RMSEA and GFI show inadequate fit, incremental fit indicators such as CFI and IFI show more positive results, indicating a good fit of the model in several aspects. NFI, TLI, and RFI show marginal fit, indicating the need for further improvement. Therefore, it is recommended that the model be adjusted to improve the overall fit. The results of the hypothesis test reveal that orientation towards supply chain disruption and supply chain quality management have no significant effect on supply chain resilience, while digital technology shows a significant positive effect on supply chain resilience. Regarding firm performance, orientation towards supply chain disruption and supply chain resilience have a significant positive effect. Still, supply chain quality management and digital technology do not consistently improve firm performance. These findings highlight the importance of digital technology and supply chain resilience in improving firm performance and indicate the need for further research to explore other factors that influence these results.